Agroforestry for biodiversity and climate change mitigation in Batutegi Protection Forest, Lampung, Indonesia (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Heryandi, Qurniati R, Darmawan A, Yuliasari V. 2022. Agroforestry for biodiversity and climate change mitigation in Batutegi Protection Forest, Lampung, Indonesia. Biodiversitas 23: 1611-1620. The conversion of protected forests into farm areas decreases biodiversity and increases greenhouse gases. Planting trees using agroforestry patterns desire to overcome these problems. This study aimed to identify plant composition, biodiversity, and calculated carbon stock values to recommend a better agroforestry development. The data collection was carried out in June 2021 from four farmer group associations at Batutegi Protection Forest Management Unit, namely Mahardika, Sinar Harapan, Hijau Makmur, and Cempaka. The agroforestry pattern applied in four Gapoktans is agrisilviculture, with a combination of crops, plantation, and forest trees. The dominant plant species are coffee, pepper, rubber, and bananas. Based on the Importance Value Index, coffee becomes the dominant crop in Hijau Makmur, Mahardika, and Sinar Harapan, while rubber is the dominant crop in Cempaka. The agroforestry pattern applied by respondents has a higher carbon stock value than the average carbon stock of coffee-based agroforestry in Indonesia, but the diversity index value is lower. Improving biodiversity is necessary to optimize growing space in farmer land through species enrichment under existing land and plant conditions.